Fractionation of Acacia seyal gum by ion exchange chromatography. (January 2020) - Apolinar-Valiente, Rafael; Williams, Pascale; Nigen, Michaël; Tamayo, Veronica Mejia; Doco, Thierry; Sanchez, Christian
Abstract: Acacia gum is a complex gum exudate from trees of selected Acacia species (i.e. A. senegal and A. seyal ). It is a continuum of molecular species showing diverse, sugar and protein composition, molar mass and charge density. Numerous studies have been conducted on several aspects of Acacia senegal gum ( Asen ), including its fractionation. Acacia seyal gum ( Asey ) has been less studied, although it has recently been gaining importance. Certain gum characteristics, such as the protein and polysaccharide composition and the molecular parameters, play a key role in the Acacia gums functionality and, hence, in their uses by food, pharmaceutical or materials industries. Our main objective is to obtain a fraction from Asey gum with high molar mass and high protein content, allowing future research works and industrial applications. Asey gum has been separated by ion exchange chromatography (IEC) into two different fractions, IEC-F1 and IEC-F2, which have been thoroughly characterized. Thus, we have succeeded to recover a protein-rich fraction with high molar mass and high intrinsic viscosity, the fraction IEC-F1. The Mark-Houwink-Sakurada analysis further indicated that fraction IEC-F1 presents more anisotropic conformation compared to fraction IEC-F2. From the partial specific volume (vs °) and the partial specific adiabatic compressibility (βs °) coefficients, a more flexible and less hydrated structure in the fraction IEC-F1 compared to Asey gum was suggested. Graphical abstract: Image 1 Highlights: Acacia seyal gum ( Asey ) has gained interest in recent years in the Acacia gum trade. Compared to Acacia senegal gum, fractionation of Asey has been less reported. The composition and structure of IEC-F1 fraction have been fully characterized. IEC-F1 is a protein-rich fraction with high molar mass and high intrinsic viscosity.